2017
DOI: 10.1101/cshperspect.a031518
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Lethal Vulnerabilities in KRAS-Mutant Cancers

Abstract: KRAS is the most commonly mutated oncogene in human cancer. Most KRAS-mutant cancers depend on sustained expression and signaling of KRAS, thus making it a high-priority therapeutic target. Unfortunately, development of direct small molecule inhibitors of KRAS function has been challenging. An alternative therapeutic strategy for KRAS-mutant malignancies involves targeting co-dependent vulnerabilities or synthetic lethal partners that are preferentially essential in the setting of oncogenic KRAS. KRAS activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 135 publications
(170 reference statements)
0
52
0
Order By: Relevance
“…Specifically, mutant KRAS increases the levels of Glucose transport 1 protein at the cell surface, leading also to an increased expression of several other molecules involved in glucose metabolism, such as hexokinase 1 and 2, phosphofructokinase 1, enolase 1, lactate dehydrogenase A, as well as molecules involved in other biosynthetic pathways (glucosamine-fructose-6-phosphate aminotransferase 1, ribulose-5-phosphate-3 epimerase, ribulose-5-phosphate isomerase, aspartate transaminase) [11,25]. In addition, the identification of synthetic lethal interactors of KRAS may provide useful targets for therapeutic intervention in KRAS-driven cancers [26][27][28][29]. To date, several functional genetic screens have identified KRAS synthetic lethal interactors with targetable potential, including kinases and other molecules involved in pathways associated with proliferation and apoptosis (extensively reviewed in [28]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, mutant KRAS increases the levels of Glucose transport 1 protein at the cell surface, leading also to an increased expression of several other molecules involved in glucose metabolism, such as hexokinase 1 and 2, phosphofructokinase 1, enolase 1, lactate dehydrogenase A, as well as molecules involved in other biosynthetic pathways (glucosamine-fructose-6-phosphate aminotransferase 1, ribulose-5-phosphate-3 epimerase, ribulose-5-phosphate isomerase, aspartate transaminase) [11,25]. In addition, the identification of synthetic lethal interactors of KRAS may provide useful targets for therapeutic intervention in KRAS-driven cancers [26][27][28][29]. To date, several functional genetic screens have identified KRAS synthetic lethal interactors with targetable potential, including kinases and other molecules involved in pathways associated with proliferation and apoptosis (extensively reviewed in [28]).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the identification of synthetic lethal interactors of KRAS may provide useful targets for therapeutic intervention in KRAS-driven cancers [26][27][28][29]. To date, several functional genetic screens have identified KRAS synthetic lethal interactors with targetable potential, including kinases and other molecules involved in pathways associated with proliferation and apoptosis (extensively reviewed in [28]). Despite being promising, oncogenic KRAS codependencies may vary between tumor types, according to the genetic background of the cell lines used and the KRAS mutation, limiting the capacity to validate the findings amongst different studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the background of mutant KRAS may be contributing to these findings as mutant HRAS or KRAS cancers are sensitive to enhanced proteotoxic stress and ER stress (De Raedt et al, 2011; Denoyelle et al, 2006). Furthermore, KRAS mutant cancers depend on several proteasome components in genome scale RNAi screens (Aguirre and Hahn, 2018; Barbie et al, 2009; Luo et al, 2009). Our studies have identified that the ubiquitin-proteasome system is a core vulnerability among a compendium of druggable targets as tested by orthogonal methods of RNA interference, CRISPR-Cas9 gene deletion or small molecule inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these large-scale efforts, very few genetic interactions have been identified in more than one study (recently reviewed 14 ). Even in the case of cancer driver genes subjected to multiple screens, such as KRAS, few genetic interactions have been identified in more than one screen 15,16 . This lack of reproducibility may be due to technical issues, e.g.…”
Section: Introductionmentioning
confidence: 99%